Onion Price Volatility and Market Integration of Different Markets in Bangladesh - Hossain, Mohammad Ismail; Billah, Muttasim; Palash, Md Salauddin; Begum, Mst Esmat Ara (Journal of the Bangladesh Agricultural University, 2025)
This study analyzed the volatility of onion prices and market integration across different markets in Bangladesh. Data were collected from the Department of Agricultural Marketing for the major ten selected onion markets (Dhaka, Mymensingh, Pabna, Faridpur, Rajshahi, Barishal, Sylhet, Khulna, Rajbari, Chattogram) from 2012 to 2022. Descriptive statistics and the Baba, Engle, Kraft, and Kroner-Generalized Autoregressive Conditional Heteroskedasticity (BEKK-GARCH) analytical techniques were used. Findings revealed that onion prices exhibit considerable variability across the selected markets. The mean prices range from BDT. 96.05 to BDT. 132.05 per quintal, with Sylhet market having the highest mean price and Rajbari market having the lowest. The distribution of onion prices is positively skewed. The kurtosis values suggest a leptokurtic distribution, indicating more extreme values than expected under a normal distribution. A clear seasonal pattern emerged in both onion arrivals and prices. Onion arrivals peak during the summer months of June, July, and August, while reaching their lowest point during the winter months of December, January, and February. Similarly, onion prices are highest during the winter months and lowest during the summer months across most markets, with slight variations. Correlation coefficients demonstrated a strong positive relationship between the price series of onions in most of the markets. Cointegration tests and the BEKK model revealed volatility spillover and coefficients indicating the relationship and degree of volatility between different markets. The Dynamic Conditional Correlation DCC model estimated significant mean, variance, asymmetric shock, and symmetric shock values for most market pairs, providing insights into the dynamics and relationships between onion markets in Bangladesh. The Department of Agricultural Marketing (DAM) should work to reduce onion price volatility by ensuring sufficient supply into the markets through encouraging production, timely supply, and import. J Bangladesh Agril Univ 23(3): 386–397, 2025